O livro de artista como dilema da preservação de acervos de arte contemporânea: entre a conservação material e a experiência do objeto - Alice Almeida Gontijo (2017)
For the artist book, the association between content, form, materials and meaning is even more evident than in the case of exclusively bibliographic collections. The artist book consciously explores the form of the book, and founds the work of art in its multiple relational possibilities, from and through this form. However, it is observed that just like what happens with traditional books, the "book character" of these works, as well as other specific characteristics that materialize the artistic proposals and ground the potential of each title, can be alienated by the conservation guidelines themselves. The management of collections of this nature by the safeguarding and exhibition institutions faces the preservation dilemma to be discussed by this research: the search for material conservation concomitant with the need for interaction with the object. If the conservation of contemporary art works has the challenge of dealing with a huge range of materials used in the elaboration of their objects, it also has the challenge of dealing with a great diversity of objects and also with the complexity of the categories in which they could be subscribed, and even with the absence of those categories. Theartist book is located in this scenario as an exemplary object for reflection on some of these challenges and on some possibilities facing them. And presents another additional difficulty: the absence of specific references inscribed in the field of preservation. In this inaugural reflective intention, the present research develops case studies, starting with the recognition of the complexity inherent to the definition of the term "artist book" and with the recognition of a between place of this extremely heterogeneouscollection. Between place this, evidenced not only by the nomenclature composed by the terms "book" and "art" whose reference range could be lost sight of but also by the inscription of the objects thus identified, in different spaces of safeguard and exhibition: that of the work of art and that of bibliographical work, in museums and libraries. In an attempt to illustrate and discuss the identified dilemma, for the development of its case studies, the research selects artist books located in different places and that bring out diverse material and conceptual issues.